PEMANFAATAN OPTIMAL SUMBERDAYA CAKALANG DI PERAIRAN MALUKU - Siahainenia, Stevanus M; Hiariey, Johanis; Baskoro, Mulyono S; Waileruny, Welem (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2017)
Overfishing has an impact on decrease of fish stocks so that it affects status of fish resource management. This research aims to analyze the optimal utilization of skipjack resources in the waters of Moluccas. Primary and secondary data were obtained through interviews and official publications. Data were analyzed through surplus production model with the techniques of CYP, and continued with the analysis of the bioeconomic model of Gordon Schaefer. The results showed that at the management regime of MSY, skipjack production reached 61.461.26 tons, with fishing effort 50,295 trips. At the open access regime, efforts increased to 84,836 trips with declining of production to 32,475.32 tons. Compared to both the MSY and open access, resource management regime at the MEY contributed to a higher economic rent, Rp 327,868,123,7700, but a lower fishing effort of 42,418 trips, and production 59,953.41 tons. Based on the bio-techno-economic values, the management regime of MEY was classified as the optimal utilization of the skipjack resources. ABSTRAK Tangkap lebih berdampak terhadap penurunan stok ikan sehingga mempengaruhi status pengelolaan sumberdaya ikan. Penelitian ini bertujuan untuk menganalisis optimalisasi pemanfaatan sumberdaya ikan cakalang di perairan Maluku. Data primer dan sekunder diperoleh melalui wawancara dan publikasi resmi. Data dianalisis melalui model surplus produksi dengan teknik CYP, dan dilanjutkan dengan analisis model bioekonomi GS. Hasil menunjukkan pada rezim pengelolaan MSY, produksi ikan cakalang mencapai 61.461.28 ton, dengan tingkat upaya penangkapan 50.184 trip. Pada rezim open access, upaya meningkat menjadi 84.683 trip dengan produksi menurun 32.416,66 ton. Dibandingkan MSY dan open access, pengelolaan sumberdaya pada rezim MEY menghasilkan rente ekonomi tertinggi Rp 328.138.580.000, upaya penangkapan yang rendah 42.341 trip, dan produksi 59.960,14 ton. Berdasarkan nilai bio-tekno-ekonomi, maka rezim pengelolaan MEY diklasifikasikan sebagai status pemanfaatan sumberdaya cakalang yang optimal. Kata kunci: Sumberdaya cakalang, pemanfaatan optimal, perairan Maluku